1999
DOI: 10.1038/sj.bmt.1701930
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis infection in allogeneic bone marrow transplantation patients

Abstract: Summary:Bone marrow transplant (BMT) recipients are prone to bacterial, viral and fungal infections. Mycobacterium tuberculosis infection can occur in these patients, but the incidence is lower than that of other infections. This report describes four patients with Mycobacterium tuberculosis infection identified from 641 adult patients who received a BMT over a 12-year period (prevalence 0.6%). The pre-transplant diagnosis was AML in two patients and CML in the other two. Pre-transplant conditioning consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
1
5

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 10 publications
1
53
1
5
Order By: Relevance
“…In fact, although marrow transplant recipients are prone to bacterial, viral and fungal infections, the incidence of Mycobacterium tuberculosis or Listeria monocytogenes infection is lower than other infections. [31][32][33][34] In agreement with other investigators, we have shown that the regeneration profiles of the ␣␤ T cell repertoire diversity after allogeneic blood and marrow transplantation are different…”
Section: Discussionsupporting
confidence: 79%
“…In fact, although marrow transplant recipients are prone to bacterial, viral and fungal infections, the incidence of Mycobacterium tuberculosis or Listeria monocytogenes infection is lower than other infections. [31][32][33][34] In agreement with other investigators, we have shown that the regeneration profiles of the ␣␤ T cell repertoire diversity after allogeneic blood and marrow transplantation are different…”
Section: Discussionsupporting
confidence: 79%
“…Tuberculosis after transplantation is a very rare infectious complication in the non-endemic area. [40][41][42] However, in endemic countries, high incidence up to 5% has been reported. 43,44 Although prevalence of tuberculosis has dramatically decreased nowadays, Korea is still a tuberculosis-endemic country.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies have reported incidences varying from 0.1 to 2.2%, while only a single study from Hong Kong has reported a much higher incidence of tuberculosis close to 5%. [2][3][4]8,9 It is generally believed that an immunosuppressed state will magnify the infectious diseases that are endemic in a locality and since Asian countries have a higher incidence of tuberculosis, one would expect the incidence of tuberculosis to be higher in such populations.…”
Section: Discussionmentioning
confidence: 99%